Om valet av preposition vid verbet forska - Lyly, Erika (Nordiske Studier i Leksikografi, 1997)
This paper considers the interaction between theory, data and lexicographical descriptions, with particular reference to constructions with prepositions. The Swedish verb forska ’to do research’ and the connected prepositional phrases i ngt, kring ngt, om ngt och på ngt (roughly ’in/ around/ about/ on sth’) are chosen as examples in order to study this interaction. The problem of the choice of preposition with the verb forska has come up in connection with the work on Svensk konstruktionsordbok, a phraseological dictionary currently in preparation at the Swedish Language Council in Stockholm. Some ofthe prepositions mentioned above have a partly overlapping usage. Even ifthese prepositions differ semantically, they are not distinct in meaning. Therefore the dictionary entry cannot simply list the constructions forska i ngt, forska kring ngt, forska om ngt and forska på ngt. There is a need to obtain a mode! by which a case such as this can be handled in lexicographic practice. The purpose of this article is to contribute to such a medel by showing on a small scale how certain aspects of the theoretical analysis of the constructions can be integrated in the dictionary entry forska.